2023
DOI: 10.1186/s12967-023-03953-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of the gut microbiota in irritable bowel syndrome: an integrated analysis based on multicenter amplicon sequencing data

Abstract: Background Gut dysbacteriosis has been reported as one of the etiologies for irritable bowel syndrome (IBS). However, the association between gut microbiota and IBS is still inconclusive. Method A paired-sample study was designed by retrieving original multicenter 16 s-rRNA data of IBS patients and healthy controls from the GMrepo database. The propensity score matching (PSM) algorithm was applied to reduce confounding bias. The differential analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The richness of Firmicutes in IBS patients compared to healthy controls is controversial. Although available evidence supports our results, which indicate higher abundance of Firmicutes in IBS patients [ 8 ], many studies have demonstrated lower richness of Firmicutes in IBS patients compared to control subjects [ 2 , 41 , 42 ]. This contentious trend was also observed for the abundance of Actinobacteria, and Faecalibacterium [ 2 , 8 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 83%
“…The richness of Firmicutes in IBS patients compared to healthy controls is controversial. Although available evidence supports our results, which indicate higher abundance of Firmicutes in IBS patients [ 8 ], many studies have demonstrated lower richness of Firmicutes in IBS patients compared to control subjects [ 2 , 41 , 42 ]. This contentious trend was also observed for the abundance of Actinobacteria, and Faecalibacterium [ 2 , 8 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies confirm the role of Sutterella in small intestine edema and in the development and progress of IBD [ 26 , 27 ]. A multicenter data analysis with 1522 amplicon samples confirms that Holdemania is enriched among IBS subjects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes, one of the major phyla in human gut microbiota, is essential for maintenance the integrity of the intestinal epithelial barrier, immune defenses against pathogenic microorganisms ( Jandhyala et al, 2015 ; Lv et al, 2023 ). Firmicutes depletion is involved in diseases with impaired intestinal barrier including irritable bowel syndrome ( Chen et al, 2023 ), colitis ( Boger-May et al, 2022 ) and Crohn’s disease ( Lv et al, 2023 ). On the other hand, Actinobacteria phylum contains numerous potential pathobionts that have the potential to cause intestinal inflammation ( Daniel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%